1997
DOI: 10.1152/ajpgi.1997.272.5.g1109
|View full text |Cite
|
Sign up to set email alerts
|

Bile salt-induced apoptosis of hepatocytes involves activation of protein kinase C

Abstract: Toxic bile salts induce hepatocyte apoptosis, a model relevant to liver injury during cholestasis. However, the signaling mechanisms culminating in bile salt-induced apoptosis remain unclear. Because protein kinase C (PKC) is activated by bile salts in hepatocytes and causes apoptosis in other cells, we tested the hypothesis that bile salt-induced hepatocyte apoptosis is mediated by PKC. The PKC inhibitors chelerythrine and Gö-6976 reduced, whereas a PKC agonist, phorbol 12-myristate 13-acetate (PMA), increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
88
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(99 citation statements)
references
References 0 publications
11
88
0
Order By: Relevance
“…BA have been shown to activate PKC in a variety of cells besides cholangiocytes. [16][17][18]46 PKC has been shown to modulate the gene expression of a number of proteins. [47][48][49][50] Our observation that BA regulate ABAT through the PKC system is novel because the mechanisms for the modulation of ABAT expression in the liver has not been previously elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…BA have been shown to activate PKC in a variety of cells besides cholangiocytes. [16][17][18]46 PKC has been shown to modulate the gene expression of a number of proteins. [47][48][49][50] Our observation that BA regulate ABAT through the PKC system is novel because the mechanisms for the modulation of ABAT expression in the liver has not been previously elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting to note that selenocompounds, which are known to inhibit L-PGDS enzymatic activity (6) and L-PGDS-induced apoptosis (13), have been shown to preferentially inhibit the calcium-dependent isoforms of PKC (4). In addition, bile salts, which are transported by L-PGDS in vivo, have been shown to activate PKC and induce apoptosis in hepatocytes (7). The possibility of other members of the MAPK family such as c-Jun NH 2 -terminal kinase and p38 MAPK participating in L-PGDS-mediated apoptosis needs to be examined so that we can more clearly define the role of the MAPK pathway in this process.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that toxic bile salt glycochenodeoxycholate induces hepatocyte apoptosis involving ligand-independent oligomerization of Fas (3) and by promoting cytoplasmic transport of Fas to the cell surface (4). PKC-dependent signaling pathways play a critical role in bile salt-induced hepatocyte apoptosis (5,6). Endoplasmic reticulum is involved in glycochenodeoxycholic acid-induced apoptosis in rat hepatocytes, although its role may be smaller than mitochondria-mediated pathway (7).…”
Section: Introductionmentioning
confidence: 99%